Equivalent efficacies of reverse hybrid and concomitant therapies in first‐line treatment of Helicobacter pylori infection. Issue 10 (31st March 2020) - Hsu, Ping‐I; Tsay, Feng‐Woei; Kao, John Y; Peng, Nan‐Jing; Tsai, Kuo‐Wang; Tsai, Tzung‐Jiun; Kuo, Chao‐Hung; Kao, Sung‐Shuo; Wang, Huay‐Min; Chen, Yan‐Hua; Shie, Chang‐Bih; Wu, Deng‐Chyang; et al.
Abstract: Background and Aim: Concomitant therapy is a recommended first‐line treatment for Helicobacter pylori infection in most national or international consensuses. Reverse hybrid therapy is a modified 14‐day concomitant therapy without clarithromycin and metronidazole in the final 7 days. This study aims to test whether 14‐day reverse hybrid therapy is non‐inferior to 14‐day concomitant therapy in the first‐line treatment of H. pylori infection. Methods: Helicobacter pylori ‐infected adult patients were randomly assigned to receive either reverse hybrid therapy (dexlansoprazole 60 mg o.d. plus amoxicillin 1 g b.d. for 14 days, and clarithromycin 500 mg plus metronidazole 500 mg b.d. for initial 7 days) or concomitant therapy (dexlansoprazole 60 mg once o.d. plus amoxicillin 1 g, clarithromycin 500 mg, and metronidazole 500 mg b.d. for 14 days). H. pylori status was assessed 6 weeks after the end of treatment. Results: Helicobacter pylori ‐infected participants ( n = 248) were randomized to receive either 14‐day reverse hybrid therapy ( n = 124) or 14‐day concomitant therapy ( n = 124). Intention‐to‐treat analysis demonstrated that the two therapies had comparable eradication rate (95.2% vs 93.5%; 95% confidence interval, −4.0% to 7.4%; P = 0.582). However, reverse hybrid therapy had a much lower frequency of adverse events than concomitant therapy (20.2% vs 38.7%, P = 0.001). The two therapies exhibited comparable drug adherence (93.5% vs 87.9%, P = 0.125). Conclusions: Fourteen‐day reverse hybrid therapy and 14‐day concomitant therapy are equivalent in efficacy for the first‐line treatment of H. pylori infection. However, reverse hybrid therapy has fewer adverse events compared with concomitant therapy.